Disparities in food insecurity between sexual minority and heterosexual adults – a higher burden on bisexual individuals - Sharareh, Nasser; Bybee, Sara; Goldstein, Evan; Jones, Shannon; Hess, Rachel; Wallace, Andrea; Seligman, Hilary; Wilson, Fernando A. (Frontiers in Public Health, 2023)
Background: Sexual minorities-individuals who identify as gay/lesbian, bisexual, or other nonheterosexual individuals-experience higher rates of food insecurity (FI) compared to heterosexual individuals. During the COVID-19 pandemic, discrimination and structural racism, which are known risk factors for food insecurity, were perpetuated against sexual and racial/ethnic minorities. However, to our knowledge, a nationally representative analysis of the impact of the pandemic on food insecurity by sexual minority status and based on race/ethnicity is missing. We aimed to determine the degree of association between FI and sexual minority adults overall, before (2019) and during (2020-2021) the pandemic, and stratified by race/ethnicity. Methods: We used nationally representative data from the 2019-2021 National Health Interview Survey (NHIS). We specified multivariable logistic regression models to determine the association between FI and identifying as a sexual minority adult (≥18 years old), including gay/lesbian, bisexual, and other non-heterosexual individuals. Results: Overall, we only observed FI disparities between bisexuals and heterosexuals (aOR 1.61 [95% CI 1.31-1.99]). Stratified by year, this association was significant only during the pandemic. Stratified by race/ethnicity, non-Hispanic white and non-Hispanic black individuals identifying as bisexual also experienced a significantly higher FI rate than their heterosexual counterparts. Conclusion: Our results may be a manifestation of the disproportionate impact of discrimination on bisexual individuals’ FI experiences. With the growing number of legislative bills targeting the rights of sexual minorities, we expect to see a higher burden of FI among bisexuals, particularly, bisexual people of color. Future intersectional research regarding FI among bisexual and racial/ethnic minority individuals would further elucidate how membership in multiple minority groups may contribute to a higher risk of FI.